Harmonic Analysis of Doubly Fed Induction Generator based Utility Interactive Wind Turbine Systems during Fault Conditions - Yasa, Yusuf; Sozer, Yilmaz; Mese, Erkan (IEEE, 2013)
This paper presents a detailed analysis of the doubly fed induction generator (DFIG) and converters by taking into account magnetic saturation of both DFIG and step-up transformer under symmetrical and asymmetrical faults. 2.5 MW DFIG is modeled through Finite Element Analysis software package and coupled with circuit and dynamic system simulators for accurate electromagnetic, drive and controller simulations. The effects of different type of utility grid faults on the DFIG rotor fluxes are analyzed and the FFT analysis of the rotor fluxes is carried to correlate the harmonic content of the rotor fluxes with the fault types. The study would provide guidance in developing advanced control and protection techniques for the DFIG system during fault conditions. The simulation results are verified with the 7.5 Hp experimental DFIG system.
Keywords: RIDE-THROUGH; Energy & Fuels; Engineering